Performance Analysis of Solar Power Generation System Using MATLAB Simulation Based on Radiation and Temperature Variations - Rini Puji Astutik; Muhammad Sabri Wahyu Febrian; Radif Rizka Andriansyah; Muhammad Rifqi Ubaidillah; Aditya bagus ainul Yaqin; Achmad Syarifudin (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
This research analyzes the performance of Solar Power Plant (PLTS) systems through MATLAB/Simulink simulations, focusing on the effects of varying solar radiation intensity and ambient temperature on the current-voltage (IV) and power-voltage (PV) characteristics of solar panels. The panel model was initially constructed based on datasheet parameters to closely replicate real-world conditions. Subsequent testing involved varying radiation (500–1000 W/m²) and temperature (20–50°C) to assess panel response under changing operational conditions. Simulation results reveal that rising temperatures significantly reduce maximum power (Pmax) due to decreasing output voltage, despite relatively stable current. Conversely, higher radiation intensity substantially increases output current, yielding greater Pmax. Radiation emerges as the dominant factor enhancing panel performance, while temperature acts as a key efficiency limiter. This simulation approach enables cost-effective analysis without field testing, serving as a reference for designing adaptive PLTS systems optimized for environmental conditions. It also provides a foundation for future studies on renewable energy modeling and control in Indonesia's tropical climate.